An experimental investigation of pump as turbine for micro hydro application - Raman N.; Hussein I.; Palanisamy K.; Foo B. (Institute of Physics Publishing, 2023)
This paper presents the results of an experimental investigation of a centrifugal pump working as turbine (PAT). An end suction centrifugal pump was tested in turbine mode at PAT experimental rig installed in the Mechanical Engineering Laboratory of Universiti Tenaga Nasional. The pump with specific speed of 15.36 (m, m3/s) was used in the experiment and the performance characteristic of the PAT was determined. The experiment showed that a centrifugal pump can satisfactorily be operated as turbine without any mechanical problems. As compared to pump operation, the pump was found to operate at higher heads and discharge values in turbine mode. The best efficiency point (BEP) in turbine mode was found to be lower than BEP in pump mode. The results obtained were also compared to the work of some previous researchers. Published under licence by IOP Publishing Ltd.